Shreds of war : fates from the Donbas frontline, 2014-2019 - Eperjesi, Ildikó; Kachura, Oleksandr; Haranʹ, O. V. (Oleksiĭ Vasylʹovych) (Stuttgart : Ibidem, 2022)
"In Eastern Ukraine, unfathomable human dramas have unfolded since 2014. Thousands died in the fighting. The homes of tens of thousands were destroyed. Many were captured and tortured, millions ousted from their homes. The lives of many were broken. Volunteers started to collect food, clothes and even weapons for the frontline. Charity organizations transferred donations to the Donets' Basin (Donbas). Priests became chaplains for soldiers. Journalists and photographers flooded into the war-zone and sometimes became involved in the events. A Hungarian and Ukrainian journalist, Eperjesi and Kachura had the opportunity to meet and talk to many of these characters. The book provides a tableau of the emblematic figures of the war in the Donbas. It not only presents tragedies, but also human moments and noble deeds. The two journalists show how the lives of ordinary people have changed as a result of the horrors of war. They also spoke to pro-Russian militiamen and even with a Russian military officer captured in Ukraine. Shreds of War is one of the few authentic books with on-the-spot coverage, interviews, and dramatic photos documenting the war in Eastern Ukraine."--
21 "It Is the Personal War of Putin and Russia Doesn't Need It" -- 22 "I'm Often Threatened Because I Am Ukrainian." -- 23 "The Local Residents Were Sitting in the Cellar. They Were Afraid That We Would Eat Them." -- 24 "There Are So Many Shattered Human Lives in the Donbas" -- 25 "Just for Spite-This Is the Mentality of the Residents of Transcarpathia. It Is Helpful in the Fights in the Donbas" -- 26 "My Helmet Caught the Bullet Meant for Me. It Remained in the Kevlar" -- 27 "Although War Is War, Ethnic Hungarian Soldiers Slaughtered a Pig on the Frontline" -- 28 "History Taught Us That You Just Cannot Get Separated from Russia Peacefully. Russia Is Russia" -- 29 "Unless Ukraine and Georgia Should Combine Forces, It Is Unlikely We Can Win This War" -- 30 "If the Russians Occupy Ukraine, Then the Next Countries to Be Occupied Will Be Slovakia, Hungary and the Czech Republic" -- 31 "People Have Discovered the Donbas for Themselves Anew" -- 32 "Children Were Born Even during the World War" -- 33 "I Buried My Whole Family" -- 34 Why Do Hungarians Fight in the Donbas? -- 35 "Russia Has Forsaken Us. Nobody Needs Us" -- 36 "The Grenade Exploded at Eye Level. The Time of the Explosion Was Written with My Blood" -- 37 "In Donetsk, Everyone Knows Where the Russian Military Intelligence Lives and Where the FSB, the Federal Security Service Is" -- 38 "We See How People May Change When They Are United. We Understand Now That We Can Assert Our Rights and Our Human Dignity.".
Print version record.
Ildi Eperjesi studied Hungarian, English, American Studies, Russian and Applied Linguistics at the universities of Budapest, Miskolc and Pécs. Since 2003, she has been a producer at the foreign desk of ATV in Budapest. Her articles have appeared in, among others, 168 Óra, Hirszerző, and Hetek. Oleksandr Kachura studied History and Ukrainian at Donetsk National University. A member of the National Union of Journalists of Ukraine, he has been working as a war correspondent in Kramatorsk since 2014. His reports have appeared in, among others, Vostochnyi farvater, Novosti Donbasa, Piotr i Mazepa, and ICTV.
eBooks on EBSCOhost
Keywords: Russo-Ukrainian War, 2014- -- Campaigns -- Ukraine -- Donbas (Region); War victims -- Ukraine -- Interviews; Soldiers -- Ukraine -- Interviews; Russo-Ukrainian War, 2014-; Guerre russo-ukrainienne, 2014-; Victimes de guerre -- Ukraine -- Entretiens; Europe -- Donets Basin; 2000-2099; interviews; Interviews; Interviews; Interviews